Method for carbide dispersion strengthening of high performance metallic materials

CN116057194BActive Publication Date: 2026-10-09BRUNEL UNIVERSITY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180054000.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2021-07-28
Publication Date
2026-10-09
Estimated Expiration
2041-07-28

Smart Images

  • Figure CN116057194B_ABST
    Figure CN116057194B_ABST
Patent Text Reader

Abstract

A method of preparing a mixture of a metal or metal alloy and (Nb x Ti 1‑x )C (where 0 < x < 1) in which (Nb x Ti 1‑x )C in particulate form is formed into a preform, either with or without metal powder, and then added to the metal if necessary. The resulting (Nb x Ti 1‑x )C / metal mixture can be heated to a temperature below the melting point of (Nb x Ti 1‑x )C and optionally dispersed in a liquid metal and / or cast and cooled to produce a solid product with improved physical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for preparing a (Nb x Ti 1-x )C preform, wherein 0 < x ≤ 1, and to a method for preparing a mixture of a metal or a metal alloy and (Nb x Ti 1-x )C, wherein 0 < x ≤ 1. More specifically, the present invention relates to a method for preparing a high-performance metal material dispersion-strengthened by ex-situ (Nb x Ti 1-x )C (wherein 0 < x ≤ 1).

[0002] The method may comprise the following steps: particle synthesis, particle compaction, infiltration of liquid metal into the compacted nanoparticle green body, processing a master alloy composed of concentrated nanoparticles engulfed by magnesium grains, diluting the master alloy to obtain nano-scale dispersion with a required particle addition rate, and finally casting the melt into a final part (e.g., castings, ingots and billets) using a practical casting process, so that nanoparticles are engulfed within grains to strengthen dispersion. The ex-situ dispersion in the alloy matrix provides improved strength, hardness, stiffness, wear resistance and enhanced corrosion resistance.

[0003] Some researchers have reported improving the properties of metal materials through particle strengthening.

[0004] The patent US7217311 B2 entitled *Method of producing metal nanocomposite powder reinforced with carbon nanotubes and the powder prepared thereby* discloses a powder metallurgy method for producing a metal matrix nanocomposite composed of a metal matrix and carbon nanotube reinforcements by a chemical method using carbon nanotube dispersion. Then, the product of metal oxide particles containing dispersed carbon nanotubes further undergoes a reduction reaction to obtain a magnesium nanocomposite added with carbon nanotubes.

[0005] The patent US 2009 / 0317622 A1 entitled *High hardness magnesium alloy composite material* describes a high-hardness magnesium alloy composite material prepared by melting nano-sized ceramic alumina into molten magnesium. The material generally contains 0.05 wt% to 2.5 wt% of ceramic particles with a size of 1 nm to 100 nm, and has a significantly increased hardness without a significant increase in weight.

[0006] WO 2017 / 173163 A1 Nanostructure self-dispersion and self-stabilization in molten metals discloses a set of manufacturing methods for incorporating nanoparticles into metallic materials, including magnesium-based nanocomposites with nanoparticles dispersed at a volume fraction greater than 3% using ultrasonic treatment.

[0007] Metallurgical Transactions https: / / doi.org / 10.1007 / BF03037835 The article "Dispersion strengthened superalloys by mechanical alloying" in [the journal name] reports a method for preparing superalloys with tightly distributed oxides and uniform internal structure through mechanical alloying by high-energy ball milling. By thermally solidifying the milled powder, the long-sought combination of dispersion strengthening and age hardening was achieved in high-temperature alloys.

[0008] Wear https: / / doi.org / 10.1016 / j.wear.2014.09.007 The article "Friction and Wear of Binder-less Niobium Carbide and The Tribological and Mechanical Properties of Niobium Carbides (NbC) Bonded with Cobalt or Fe3Al" reports the use of NbC bulk materials and NbC bulk materials bonded with cobalt and Fe3Al via powder metallurgy and liquid infiltration hot pressing as cutting tool materials. Test samples of NbC and / or NbC-bonded systems exhibit high hardness and wear resistance.

[0009] Acta Materialia https: / / doi.org / 10.1016 / S1359-6454(01)00389-5 The article "Precipitation of NbC in a model austenitic steel" reported strain-induced NbC precipitation through thermomechanical treatment. This in-situ formation of nano-NbC precipitation (~10 nm) indicates that the steel is strengthened through a dislocation pinning effect (Aurorwan strengthening).

[0010] US Patent 4180401, "Sintered steel alloy," discloses a sintered steel alloy (based on powder metallurgy) for hot-working tool applications, comprising a hard metal compound (carbide) and a nickel martensitic steel matrix alloy. In this patent, the addition of carbides is up to 50%, and the selected carbides are TaC, ZrC, CrC, VC, NbC, and WC. This steel achieves a high hardness of 65-70 Rockwell C.

[0011] US 7686896 B2 High-strength steel sheet excellent in deep drawing characteristics and method for production thereof discloses a high-strength steel with excellent deep drawing characteristics and a method for producing thereof, which uses strain-induced NbC precipitation to further strengthen the steel sheet without sacrificing the isotropic mechanical properties during the deep drawing process.

[0012] International Journal of Refractory Metals and Hard Materials( https: / / doi.org / 10.1016 / j.ijrmhm.2016.04.021 The article "Stainless steel bonded NbC matrix cermets using a submicron NbC starting powder" reports the complete densification of NbC cermets with ferritic and austenitic stainless steel binders via pressureless liquid-phase sintering. The binder content and heat treatment allow for tuning the microstructure and mechanical properties of NbC-based hard cermets for cutting tool applications.

[0013] US patent 8043068B2, "Ni-Fe based super alloy, process of producing the same and gas turbine," discloses a Ni-Fe based super alloy, a method for producing the Ni-Fe based super alloy, and a gas turbine manufactured by casting. The alloy contains 1.5% to 5.0% Nb and no more than 0.03 wt% C. In-situ formed nano-NbC precipitates are activated by heat treatment following casting.

[0014] US Patent 9249488B2 discloses a nickel-based dual multi-phase intermetallic compound alloy containing Nb and C, and a manufacturing method for obtaining Nb and C by adding NbC to a nickel-based melt to decompose NbC. The decomposed C and Nb are considered key factors for improving high-temperature mechanical properties.

[0015] US patent 9017490B2, "Ultra high strength alloy for severe oil and gas environments and method of preparation," discloses an ultra high strength alloy for use in harsh oil and gas environments and its preparation method, wherein the Nb content is 4.0-6.5 wt%. The Nb / (Ti+Al) ratio is between 2.5 and 7.5 to provide the desired volume fractions of γ′ and γ″ phases. Additional Nb can combine with C to form in-situ NbC nanoparticles for further strengthening.

[0016] The article Wear-resistant alloy for the protection of the contact surfaces of the blades of aircraft engines against oxidation at high temperature in Nauka Innovats 10 (2014):22-31 reports a ThTN-62 alloy with eutectic composition in a Co-NbC quasi-binary cross section, which has in-situ formed NbC as a reinforcing agent and good heat resistance.

[0017] Journal of Materials Science, Vol. 9, 1974, J. Sautereau, “Sintering Behaviour of Ultrafine NbC and TaC Powders”, pp. 761-771, discloses the sintering behavior of NbC and TaC in Ar or H2 atmosphere, including the compression and sintering of NbC powder to form spheres.

[0018] GB 1417261 (Daido Seiko KK) discloses a method for forming a carbide "reinforced" layer on the surface of molten metal. This forms a ceramic layer on top of the metal, with a clear boundary layer between the two layers.

[0019] WO 2009 / 082180 A2 (Seoul National University Industry Foundation) discloses a fully solid solution powder for preparing metal-ceramic composite sintered bodies and a method thereof. In particular, this invention relates to a fully solid solution powder and a method for preparing it, which can significantly improve the toughness of metal-ceramic sintered bodies used in high-speed cutting tool materials and mold materials in metal processing fields (e.g., various machinery and automotive industries).

[0020] KR 20100107478 A discloses a similar subject matter to WO 2009 / 082180 A2 and is owned by the same applicant. Due to the presence of metal oxides that require reduction treatment, it requires a step of reduction, carbonization or reduction, carbonization and nitridation of the mixed powder.

[0021] Most of the above-mentioned methods related to magnesium composite materials are based on powder metallurgy process, which is difficult to be applied industrially due to high raw material cost. In the case of the aforementioned melting processing methods, it requires additional external fields, such as ultrasonic treatment or electromagnetic stirring, which is also a cost-ineffective method. Most importantly, as Figure 1 (a) shows, during solidification, the melting processing process causes particle aggregation and segregation to the grain boundary region, which is detrimental to mechanical properties.

[0022] In a first aspect of the present invention, there is provided a method for preparing a mixture of a metal or a metal alloy and (Nb x Ti 1-x )C, wherein 0 < x ≤ 1, comprising the following steps:

[0023] (Ai) providing (Nb x Ti 1-x )C in the form of particles,

[0024] (Aii) mixing said (Nb x Ti 1-x )C with particles of a metal or a metal alloy,

[0025] (Aiii) forming said particles into a preform by compression or by placing said particles in a mold,

[0026] (Aiv) optionally adding said preform to a metal or a metal alloy, and

[0027] (Av) optionally heating said preform to a temperature below the melting point of (Nb x Ti 1-x )C;

[0028] or

[0029] (Bi) providing (Nb x Ti 1-x )C in the form of particles,

[0030] (Bii) forming said particles into a preform by compression or by placing said particles in a mold, and

[0031] (Biii) adding said preform to a metal or a metal alloy, and

[0032] (Biv) Optionally, the mixture is heated to below (Nb) x Ti 1-x The melting point of C is the temperature at which metals or metal alloys are melted.

[0033] If the particles are compressed to form a preform, the method may include the step of varying the compression applied to the particles to produce a preform containing voids, wherein the void ratio is 1% to 75% of the preform, preferably 30% to 75% of the preform.

[0034] Preferably, x is 0.01 to 1. More preferably, x is 0.8 to 1. Most preferably, x is 0.9 to 1.

[0035] In a preferred embodiment, the preform is shaped into a specific shape by forming the preform into the shape, or by an additional step including removing a portion of the preform to produce a preform having the shape, or a combination thereof. For example, the preform can be shaped by drilling or machining (or both).

[0036] Prefabs can then be used in various ways to incorporate (Nb) x Ti 1-x C is combined with metals or metal alloys to provide alloys with excellent properties.

[0037] Since x is defined as non-zero, TiC is excluded from the scope of this invention. It has been found that pure TiC leads to the formation of agglomerates, which is disadvantageous.

[0038] With (Nb x Ti 1-x The advantages of Ti existing in the form of C include:

[0039] 1. It can reduce the density of NbC, which helps to make the alloy lighter (in addition to the machinability benefits already described).

[0040] 2. Because Ti is cheaper than Nb, the material cost can be lower.

[0041] 3. Increased thermal resistance. For example, pure NbC can be oxidized in air at temperatures above 500°C, while TiC exhibits good atmospheric oxidation resistance up to approximately 1200°C.

[0042] This invention enables the manufacture of metallic materials in which nanoscale or microscale particles are engulfed by grains, providing superior mechanical properties compared to bulk alloys, with scale-up capabilities and reduced costs, because the method does not rely on the use of conventional external field treatments, powder metallurgy, and / or chemical reactions.

[0043] It has been discovered (Nb) x Ti 1-xC possesses unique and beneficial properties, such as excellent wetting ability, self-dispersibility, stability of colloidal suspensions, and spontaneous engulfment during the master alloy manufacturing stage. Furthermore, the inventors have discovered that actual cast products manufactured from colloidal solutions maintain excellent uniform distribution of nanoparticles (dispersions) within the magnesium alloy grains without segregation (e.g., ...). Figure 1 (b) shown), and has improved mechanical properties.

[0044] Not wanting to be bound by theory, it has been discovered (Nb x Ti 1-x C can be used with some metals, but not with others. For example, this invention is not applicable to pure aluminum because aluminum reacts with (Nb) x Ti 1-x The reaction is called C. Therefore, in a preferred embodiment, the invention is limited to applications that do not react with (Nb) x Ti 1-x A metal / metal alloy reacted with C. The metal or metal alloy is preferably magnesium.

[0045] It is also believed that when (Nb) x Ti 1-x The invention is most effective when C can wet the metal and thus facilitate dispersion. Wettability can be analyzed using Brownian motion (kT) and van der Waals gravity, where k is the Boltzmann constant (1.3807 × 10⁻²³ J·K). -1 And T is the Kelvin temperature. One possible factor affecting wettability is (Nb) x Ti 1-x C. Particle size. Therefore, in a preferred embodiment, the average size of the particles is 10 nm to 10 μm.

[0046] The method preferably includes the step of varying the compression applied to the particles to produce a preform comprising voids, wherein the void fraction is 1% to 75% (preferably 30% to 75%) of the preform. The relationship between compression and void fraction is well known (e.g., in the ceramics field), so there is no difficulty for those skilled in the art in controlling the compression to achieve the target void fraction.

[0047] The preferred upper limit for the porosity of the preform is 75%, because exceeding this limit makes it practically impossible to manufacture the preform due to the lack of physical contact between the particles required to hold them together as a monolithic preform. The preferred lower limit for the porosity of the preform is 30%, because below this limit, the particles fuse together, and there is a risk of grain growth, resulting in poor permeability and reduced hardening. The presence of porosity allows liquid metal / metal alloys to permeate into the voids to form a permeated preform. Samples permeated (and subsequently air-cooled) within the preferred range exhibit significantly higher hardness than samples loaded at values ​​above the preferred range.

[0048] Preferably, control (Nb) x Ti 1-x The ratio of C to metal or metal alloy to make (Nb) x Ti 1-x The amount of C is 1 wt% to 100 wt% of the final product (preferably 1 wt% to 80 wt%).

[0049] In one implementation, in step (Ai) or step (Bi), (Nb) x Ti 1-x C particles with melting points lower than (Nb) x Ti 1-x The NbC preform is obtained by mixing a substance that can be an organic binder (e.g., polyvinyl alcohol-PVA) that is soluble in water and then mixed with carbide powder to produce a slurry. The slurry is then cast into a mold, and the water and PVA are burned off at high temperature.

[0050] For Mg alloys, the "MAGREX-60" flux can be used to protect the molten magnesium alloy from oxidation. It can also be mixed with NbC and introduced into liquid Mg.

[0051] The mixture of preform and metal / metal alloy can be formed at a temperature below the melting point of the preform by adding the preform to a liquid metal or metal alloy. Alternatively, the preform can be added to a solid metal or metal alloy (e.g., in powder form), and the mixture can be heated to melt the metal / metal alloy.

[0052] Alternatively, it can form a group including (Nb) x Ti 1-x A preform of C and metal or metal alloy particles, and the preform can be heated to a temperature below (Nb) x Ti 1-x The temperature of the melting point of C is used to melt the metal or metal alloy particles.

[0053] Metals or metal alloys and (Nb) can be used. x Ti 1-x)C, the resulting mixture is added to a liquid metal or metal alloy, and the mixture is dispersed in the liquid metal or metal alloy. Alternatively, it may be added to a metal or metal alloy in solid form, for example in powder form, and the mixture is heated to melt the metal / metal alloy. The dispersed mixture can then be cast to form a solid product.

[0054] Advantageously, it has been found that the present method enables the formation of a solid solution of metal alloy with nanoparticle dispersion within the alloy grains rather than at the grain boundaries (see Figure 1 ). Furthermore, it has been found that this solid solution alloy dispersion has a relationship close to the theoretical relationship between the volume fraction of (Nb x Ti 1-x )C and hardness / stiffness, that is, a linear relationship. In contrast, conventional dispersions having nanoparticles at grain boundaries have a non-linear relationship between the volume fraction of (Nb x Ti 1-x )C and hardness / stiffness.

[0055] In another aspect of the present invention, there is provided a method for preparing a (Nb x Ti 1-x )C preform, wherein 0 < x ≤ 1, comprising the following steps:

[0056] (i) providing (Nb x Ti 1-x )C in particulate form, and

[0057] (ii) forming the particles into a preform.

[0058] The particles may be compressed to form a preform, or the particles may be placed in a mold to form a preform.

[0059] Now a plurality of preferred embodiments of the present invention will be described with reference to the accompanying drawings and as shown in the accompanying drawings, wherein:

[0060] Figure 1 a and Figure 1 b are schematic diagrams showing (a) segregation of nanoparticles to grain boundaries in conventional melt-processed metal matrix composites and (b) dispersion of nanoparticles within magnesium grains rather than at grain boundaries, whereby these nanoparticles provide much-needed dispersion strengthening;

[0061] Figure 2 is an image of a pressureless infiltrated NbC sphere with a diameter of 32 mm;

[0062] Figure 3A cross-sectional photograph of the cured metal from an 87.5 vol% Mg-12.5 vol% NbC colloidal solution is shown, revealing a macroscopically uniform particle distribution and spatial variation of the average Vickers hardness from top to bottom (along the direction of gravity) of the cured metal. The hardness values ​​exhibit a narrow range of 80 HV3 to 93 HV3 (Nb... x Ti 1-x Good dispersion of C particles.

[0063] Figure 4 It shows the result of Figure 3 Polarized optical microstructure of hardened billets formed from master alloys; color contrast represents individual grains;

[0064] Figure 5 Tensile stress-strain curves were plotted for magnesium alone and magnesium with an 11% NbC master alloy;

[0065] Figure 6 The AZ91 alloy and the addition of 3 vol% (Nb) were depicted. x Ti 1-x Tensile stress-strain curves of AZ91 alloy with C particles in the as-cast and T6 conditions;

[0066] Figure 7 Polarized optical microstructures of AZ31 alloys (a) without and (b) with 0.2% NbC particles, showing grain refinement, are shown. The color contrast represents individual magnesium grains;

[0067] Figure 8 Stiffness (elastic modulus) is added to magnesium alloys (Nb). x Ti 1-x A graph of the percentage function of C;

[0068] Figure 9(a) shows the x=1 (Nb) infiltrated by liquid nickel alloy in a pressureless environment. x Ti 1-x Image of sphere C;

[0069] Figure 9(b) is an image with a higher magnification than Figure 9(a), showing the (Nb) at x=1 in a nickel alloy matrix. x Ti 1-x Uniform distribution of C particles;

[0070] Figure 9(c) shows the Nb alloy matrix with x = 0.9. x Ti 1-x Image showing uniform distribution of C particles;

[0071] Figure 9(d) shows scanning electron microscope images and the chemical elemental spectra of Ti, Nb, C, Ni, Cr, and Fe in the sample. The top left figure shows the Nb content at x = 0.8 in the nickel alloy matrix. x Ti 1-x Distribution of C particles;

[0072] Figure 10(a) shows the Nb matrix with x=1 in the steel matrix. x Ti 1-x Scanning electron microscope image of uniformly distributed C particles;

[0073] Figure 10(b) shows the Nb content in the steel matrix at x = 0.9. x Ti 1-x Scanning electron microscope image of uniformly distributed C particles;

[0074] Figure 11(a) shows the Nb matrix with x=1 in the Co matrix. x Ti 1-x Scanning electron microscope image of uniformly distributed C particles;

[0075] Figure 11(b) shows the Nb content in the Co matrix at x = 0.9. x Ti 1-x Scanning electron microscope image of uniformly distributed C particles;

[0076] Figure 12 This shows a scanning electron microscope image of NbC particles in an Ag matrix; and

[0077] Figure 13 This image shows the microstructure of NbC particles in an Al-Mg alloy. Example

[0078] Example 1: Synthesis of solid solution particles and nanoparticles

[0079] (Nb) x Ti 1-x The initial nominal components of C (x = 0.9, 0.85, 0.8, 0.5, 0.2, 0.1) were mixed, compressed, and heat-treated at a high temperature of ~2000℃ in an Ar atmosphere. The intermediate products were then ground to obtain a solid solution phase.

[0080] Example 2: Liquid magnesium was permeated into solid solution carbide spheres without pressure.

[0081] Solid solution particles (Nb) with particle sizes ranging from 300 nm to 2 μm were compressed under pressures of 1 ton and 2 tons. x Ti 1-xC(x=1) was used to produce spheres with diameters of 16mm × thicknesses of 5mm and 32mm × thicknesses of 10mm, respectively. The green spheres were preheated at 200°C for 2 hours and then placed in liquid magnesium at 700°C. It was observed that, without any external pressure, the liquid magnesium completely penetrated the interior of the 16mm diameter sphere within 30 minutes and the 32mm diameter sphere within 60 minutes. The penetrated spheres were then cooled in a protective atmosphere. The 32mm diameter penetrated sphere... Figure 2 The permeated Mg / (Nb) is shown in the figure. x Ti 1-x The average Vickers hardness (HV0.1) of the C (x=1) sphere was 325, compared to an average Vickers hardness (HV0.1) of 26.5 for the reference magnesium matrix. The estimated volume fraction of NbC in the infiltrated sphere was in the range of 50% to 60%.

[0082] Example 3 Preparation of magnesium-(Nb) x Ti 1-x C master alloy

[0083] Compressing Nb with a diameter of 32 mm × thickness of 10 mm and a particle size ranging from 300 nm to 2 μm under a uniaxial pressure of 1-2 tons. x Ti 1-x C(x=1) solid solution green pellets were preheated at 200°C for 2 hours, and then subjected to pressureless infiltration for 1 hour in various liquid magnesium alloys (e.g., commercially pure magnesium, AZ31 alloy, Elekto 21, and AZ91D alloy). The melt containing the pellets was then gently stirred at 500 rpm to break up the pellets and disperse (Nb) x Ti 1-x )C particles, thereby obtaining well-dispersed Mg-(Nb) x Ti 1-x Colloidal solutions of Mg were prepared using this method. After holding for 2 hours, these concentrated solutions were cooled under a protective atmosphere to allow the nanoparticles to be encapsulated by the Mg matrix, resulting in different levels of (Nb)-C colloidal solutions. x Ti 1-x Solid master alloys of C particles (Table 1).

[0084] Table 1

[0085] List of Mg master alloys composed of NbC particles

[0086]

[0087]

[0088] For some samples produced in Example 3, the hardness and elastic modulus have been measured and are listed in Table 2. This demonstrates that materials with both high modulus and high hardness can be produced.

[0089] Table 2 Mechanical properties of solid solution reinforced magnesium metal matrix composites

[0090]

[0091] Dispersed from 12.5 vol% (Nb) x Ti 1-x The magnesium master alloy composed of C (x=1) has a Vickers hardness of 87.0 HV3 and an elastic modulus of 122.5 GPa. The measured Vickers hardness and elastic modulus of a reference magnesium material are 34.5 HV3 and 41.0 GPa, respectively.

[0092] Contains 12.5 vol% (Nb) x Ti 1-x The average Vickers hardness value of the C master alloy varies within a narrow range of 87±8HV3 from top to bottom (i.e., along the direction of gravity). Figure 3 As shown. The uniform hardness throughout the sample indicates the absence of particle precipitation, which further demonstrates the stability of the colloidal solution with well-dispersed particles in Mg. Similarly, containing 11 vol% (Nb) x Ti 1-x The average Vickers hardness of the C master alloy is 74 ± 8 HV3. It contains 11 vol% dispersed (Nb) x Ti 1-x The magnesium master alloy with C(x=1) exhibits a tensile yield strength of 137.8 MPa and an ultimate strength of 165.4 MPa, while a reference magnesium material under the same conditions shows a yield strength of 16.4 MPa and an ultimate strength of 70.5 MPa. The tensile stress-strain curves are shown below. Figure 5 As shown.

[0093] like Figure 4 As shown, a uniform distribution of particles engulfed by Mg grains was also observed. These engulfed particles interact with dislocations and can contribute significant strength through the Orovan strengthening mechanism. Compared to conventional magnesium-based metal matrix composites produced by conventional casting methods, the particle engulfment feature observed here is (Nb x Ti 1-x The unique properties of the C / Mg system make it more difficult to achieve engulfment in conventional casting methods.

[0094] Example 4: Preparation of diluted Mg / (Nb) x Ti 1-x C. Colloidal Solution Method

[0095] The (100-y)Mg+y(Nb) prepared in Example 3 was used. x Ti 1-x The master alloy of C (x = 1 and y = 5 vol%, 11 vol%, 12.5 vol%) was preheated to 200 °C and then added to liquid Mg alloy (AZ91D) to obtain 1 vol%, 2 vol%, and 3 vol% (Nb) compositions. x Ti 1-x C. The melt was protected under an SF6+N2 gas flow to prevent oxidation. The melt was gently stirred with a metal rod and then mixed by an impeller at 100-200 rpm to ensure no turbulence or oxide inclusions were generated during mixing. The stability of the colloidal solution with 3 vol% particles was investigated at holding times of 15 min and 30 min. The microhardness (HV0.1) of the entire cured preform was measured to be 70 ± 5. The low variation indicates the absence of particle precipitation.

[0096] The solution prepared in this method is fed into various die-casting processes, such as gravity die casting, twin-roll casting, and high-pressure die casting, to obtain the final product, wherein during the solidification process (Nb x Ti 1-x The C particles were continuously engulfed by the Mg matrix.

[0097] Example 5: Solid solution nanoparticle-reinforced AZ91 alloy

[0098] Following the method described in Example 4, 3 vol% solid solution nanoparticles were introduced into liquid AZ91 magnesium alloy (9 wt% Al, 0.8 wt% Zn, and 0.2 wt% Mn) by diluting a magnesium master alloy containing 12.5 vol% solid solution nanoparticles to form a particle dispersion-strengthened AZ91 alloy. The introduced solid solution nanoparticles had a particle size range of 300 nm to 2 μm and were uniformly dispersed in the AZ91 magnesium alloy matrix. Under as-cast conditions, the nanoparticle-strengthened AZ91 alloy exhibited a tensile yield strength of 125 MPa and an ultimate tensile strength of 179 MPa, while the AZ91 alloy without added particles showed a yield strength of 102.2 MPa and an ultimate tensile strength of 150.9 MPa. After T6 heat treatment (i.e., 413℃ for 16 hours and 168℃ for 16 hours), the solid solution nanoparticle-reinforced AZ91 alloy exhibits a tensile yield strength of 161.5 MPa and an ultimate strength of 240.6 MPa, while the reference AZ91 alloy achieves a yield strength of 129.7 MPa and an ultimate strength of 232.1 MPa. The stress-strain curves of the solid solution-reinforced AZ91 alloy and the reference AZ91 alloy are shown below. Figure 6 As shown.

[0099] Example 6 Grain Refining of AZ31 Magnesium Alloy

[0100] NbC particles can also enhance heterogeneous nucleation of magnesium grains during the curing process. Grain refinement tests have been conducted on AZ31 magnesium alloy using NbC particles with a size of 2 μm. For this purpose, the master alloy prepared in Example 3 was added to liquid AZ31 alloy held at 40°C under superheat, and gently stirred manually. After holding for 10 minutes, the mixture was cast into a steel mold. The grain size of the solid solution-refined AZ31 was 198 ± 14 μm, compared to 464 ± 97 μm for the reference AZ31. The microstructure is shown below. Figure 7 As shown.

[0101] Example 7: Manufacturing a product containing 3 vol% (Nb) 0.85 Ti 0.15 )C's diffusion-enhanced AZ91

[0102] 3 vol% (Nb) under a 1-ton load 0.85 Ti 0.15 C solid solution particles were compressed into spheres (32 mm in diameter) and then introduced into liquid AZ91 magnesium alloy (9 wt% Al, 0.8 wt% Zn, and 0.2 wt% Mn). The particles were dispersed in the liquid magnesium alloy by gentle stirring. This colloidal solution was cast into a permanent mold. Under as-cast conditions, the tensile yield strength of the particle-reinforced AZ91 alloy was observed to be 133.8 MPa and the ultimate tensile strength to be 172.4 MPa, while the yield strength and ultimate tensile strength of the AZ91 alloy without particles were 120.8 MPa and 150.9 MPa, respectively.

[0103] Example 8 Stiffness as (Nb) x Ti 1-x The function of C particle number

[0104] Figure 8 It shows Mg / (Nb) x Ti 1-x The graph shows the elastic modulus of the C composite material as a function of the added particles (blue line represents experimental data, red line represents theoretical data). Dispersion-strengthened Mg alloys were produced as in Examples 3, 4, and 5.

[0105] Using the concept of mixing laws, the measured modulus is similar to the predicted value. In conventional metal matrix composites, the predicted value differs greatly from the measured value due to the aggregation and segregation of reinforcing particles at grain boundaries. If the particles are uniformly distributed in the matrix (as in this invention), then the value increases linearly with the volume fraction of particles.

[0106] The results in the figure show that alloys with different moduli (stiffness) can be designed.

[0107] Example 9: A method for strengthening nickel-based superalloys by introducing compression balls into a nickel-based alloy melt.

[0108] The average particle size (Nb) is approximately 1.2 micrometers when compressed under pressure of 0.5 tons or 1 ton. x Ti 1-x C (x = 1, 0.9, and 0.8) was used to produce spheres with a diameter of 6 mm and a thickness of 1.1 mm. The estimated porosities of the green bodies were 55% and 49% for 0.5 ton and 1 ton loads, respectively. The green body spheres were placed on a layer of nickel-based Inconel 718 alloy powder in an Al2O3 crucible.

[0109] In an Ar atmosphere of 5N purity (flow rate 0.2 L / min), the temperature was raised to 1450 °C at a rate of 3 K / s, bringing the Ni alloy to a molten state. For each loading condition, the melt of one set of samples was held for 60 s, and the melt of another set of samples was held for 180 s, then cooled to room temperature at a rate of 10 K / s. During this period, the sphere sank into the liquid metal, and then pressureless permeation was clearly observed, and (Nb x Ti 1-x The C-sphere was completely wetted with liquid nickel alloy.

[0110] Figure 9(a) shows an electron microscope image at a lower magnification of x=1, and Figure 9(b) shows an image at a higher magnification. In Figure 9(a), it can be seen that liquid Ni has penetrated into the green pellets and filled the pores within them. In Figure 9(b), the uniform dispersion of NbC particles in the nickel alloy matrix can be seen. Figure 9(c) shows the NbC particles at x=0.9. x Ti 1-x The microstructure of (Nb)C. Figure 9(d) shows the microstructure of (Nb)C with x = 0.8. x Ti 1-x Chemical element diagram of the alloy composed of C particles. In this chemical spectrum analysis, Nb solid solution (Nb) is present in the Inconel 718 matrix. x Ti 1-x The coexistence of C-phase particles is clearly visible.

[0111] Example 10: A method for strengthening cast iron, tool steel, and stainless steel by introducing compressed balls into an alloy melt.

[0112] The average particle size (Nb) is approximately 1.2 micrometers when compressed under pressure of 0.5 tons or 1 ton. x Ti 1-x C(x = 1 and 0.9) was used to produce spheres with a diameter of 6 mm and a thickness of 1.1 mm. The estimated porosities of the green bodies were 55% and 49% for 0.5 ton and 1 ton loads, respectively. The green spheres were placed on a layer of 316L alloy powder in an Al2O3 crucible.

[0113] In an Ar atmosphere of 5N purity (flow rate 0.2 L / min), the temperature was raised to 1500 °C at a rate of 3 K / s, bringing the 316L alloy to a molten state. For each loading condition, the melt of one set of samples was held for 60 s, and the melt of another set of samples was held for 180 s, then cooled to room temperature at a rate of 10 K / s. During this period, the sphere sank into the liquid metal, and then pressureless permeation was clearly observed, and (Nb x Ti 1-x The C-shaped ball was completely wetted by the liquid alloy.

[0114] Figure 10(a) shows an electron microscope image at a high magnification, where x = 1 (Nb x Ti 1-x The uniform dispersion of C particles in the steel matrix is ​​clearly visible.

[0115] Figure 10(b) shows an electron microscope image at a higher magnification, where x = 0.9 (Nb x Ti 1-x The uniform dispersion of C particles in the steel matrix is ​​clearly visible.

[0116] Example 11: A method for strengthening cobalt by introducing compressed balls into the melt.

[0117] The average particle size (Nb) is approximately 1.2 micrometers when compressed under pressure of 0.5 tons or 1 ton. x Ti 1-x C (x = 1 and 0.9) was used to produce spheres with a diameter of 6 mm and a thickness of 1.1 mm. The estimated porosities of the green bodies were 55% and 49% for 0.5 ton and 1 ton loads, respectively. The green spheres were placed on a layer of Co powder in an Al2O3 crucible.

[0118] In an Ar atmosphere of 5N purity (flow rate 0.2 L / min), the temperature was raised to 1600 °C at a rate of 3 K / s, causing the Co powder to melt. For each loading condition, the melt of one set of samples was held for 60 s, and the melt of another set of samples was held for 180 s, then cooled to room temperature at a rate of 10 K / s. During this period, the spheres sank into the liquid metal, and then pressureless permeation was clearly observed, and (Nb x Ti 1-x ) The C-sphere was completely soaked in liquid metal.

[0119] Figure 11(a) shows an electron microscope image where x = 1 (Nb x Ti 1-x C particles are uniformly dispersed in the Co matrix.

[0120] Figure 11(b) shows an electron microscope image where x = 0.9 (Nb x Ti1-x C particles are uniformly dispersed in the Co matrix.

[0121] Table 3

[0122] Vickers hardness (HV1) of NbC-hardened Co, 316L, and IN718 alloys

[0123] Co 146.8 873.5 970.9 316L 126.7 554.8 612.1 IN718 288.7 725.2 782.0

[0124] Example 12: A method for strengthening silver by introducing compressed balls into the melt.

[0125] NbC with an average particle size of approximately 1.2 micrometers was compressed under a pressure of 0.25 tons to produce spheres with a diameter of 6 mm and a thickness of 1.1 mm. The estimated porosity of the green body was 55%. The green bodies (spheres) were placed on a layer of Ag powder in an Al2O3 crucible.

[0126] In an Ar atmosphere of 5N purity (flow rate of 0.2 L / min), the temperature was raised to 1200 °C at a rate of 3 K / s, bringing the Ag powder to a molten state. The melt was held for 60 s and then cooled to room temperature at a rate of 10 K / s. During this period, the spheres sank into the liquid metal, and pressureless permeation was then clearly observed, with the NbC spheres completely wetted by the liquid metal.

[0127] Figure 12 Electron microscope images are shown, revealing NbC particles within an Ag matrix. The hardness (HV) of pure Ag and Ag + 36 vol% NbC is also shown. 0.1 The values ​​are 40 and 158 respectively.

[0128] Example 13: A method for strengthening aluminum alloys by introducing a Mg-NbC master alloy.

[0129] When NbC was added directly to liquid aluminum, a chemical reaction was observed between NbC and liquid aluminum. To minimize the chemical reaction, the master alloy prepared according to Examples 2 and 3, having a composition of 50 wt% Mg and 50 wt% NbC, was placed in a liquid Al melt.

[0130] The melt was held at 730°C for 2.5 hours and then cast into a steel mold. The microstructure of the cast sample showed the dispersion of NbC particles. The hardness (HV) of pure Al was... 0.1 The hardness (HV) of NbC-containing aluminum was observed to be 22. 0.1 The range is 100 to 250, depending on the local concentration of NbC content.

[0131] Figure 13 Images showing the microstructure of NbC particles in an Al-Mg alloy are presented.

[0132] All optional and preferred features and modifications of the described embodiments and dependent claims can be used in all aspects of the invention taught herein. Furthermore, the various features of the dependent claims, as well as all optional and preferred features and modifications of the described embodiments, can be combined and interchanged with each other.

[0133] This application claims priority to UK patent application No. 2011863.4, the disclosure of which and its accompanying abstract are incorporated herein by reference.

Claims

1. A method for preparing a mixture of metal or metal alloy and (Nb x Ti 1-x )C, wherein 0 < x ≤ 1, comprising the following steps: (Ai) provides (Nb) in particulate form x Ti 1-x C, (Aii) will refer to (Nb) x Ti 1-x C is mixed with particles of metal or metal alloy. (Aiii) The particles are compressed to form a preform to produce a preform containing voids, wherein the porosity is 30% to 75% of the preform, and wherein the particles do not fuse together. (Aiv) Optionally, the preform is added to a metal or metal alloy, and (Av) Heat the preform to below (Nb) x Ti 1-x The temperature of the melting point of C, so as to melt the metal or metal alloy; or (Bi) provides (Nb) in particulate form x Ti 1-x C, (Bii) The particles are compressed to form a preform to produce a preform containing voids, wherein the porosity is 30% to 75% of the preform, and wherein the particles do not fuse together. (Biii) Adding the preform to a metal or metal alloy, and (Biv) Heat the mixture to below (Nb) x Ti 1-x The melting point of C is the temperature at which metals or metal alloys are melted; It also includes metals or metal alloys and (Nb) x Ti 1-x The steps of adding the mixture obtained in step C to a liquid metal or metal alloy and dispersing the mixture in the liquid metal or metal alloy, and... It also includes the step of casting the dispersed mixture to produce a master alloy. The metal or metal alloy mentioned therein is magnesium.

2. A method for preparing a mixture of metal or metal alloy and (Nb x Ti 1-x )C, wherein 0 < x ≤ 1, comprising the following steps: (Ai) provides (Nb) in particulate form x Ti 1-x C, (Aii) will refer to (Nb) x Ti 1-x C is mixed with particles of metal or metal alloy. (Aiii) The particles are compressed to form a preform to produce a preform containing voids, wherein the porosity is 30% to 75% of the preform, and wherein the particles do not fuse together. (Aiv) Optionally, the preform is added to a metal or metal alloy, and (Av) The preform is heated to a temperature below the melting point of (NbxTi1-x)C to melt the metal or metal alloy; or (Bi) provides (Nb) in particulate form x Ti 1-x C, (Bii) The particles are compressed to form a preform to produce a preform containing voids, wherein the porosity is 30% to 75% of the preform, and wherein the particles do not fuse together. (Biii) Adding the preform to a metal or metal alloy, and (Biv) Heat the mixture to below (Nb) x Ti 1-x The melting point of C is the temperature at which metals or metal alloys are melted; It also includes metals or metal alloys and (Nb) x Ti 1-x The steps of adding the mixture obtained in step C to a liquid metal or metal alloy and dispersing the mixture in the liquid metal or metal alloy, and... It also includes the steps of casting and cooling the dispersed mixture to produce a solid product. The metal or metal alloy mentioned therein is magnesium.

3. The method of claim 1 or 2, wherein the average size of the particles is 10 nm to 10 μm.

4. The method of claim 1 or 2, wherein x is from 0.01 to 1.

5. The method of claim 1 or 2, wherein the preform having the desired shape is formed by the steps of: forming the preform into the shape or by an additional step including removing a portion of the preform to produce a preform having the shape, or a combination thereof.

6. The method of claim 5, wherein the removal step is performed by drilling or machining the preform.

7. The method of claim 1 or 2, wherein the (Nb) x Ti 1-x The ratio of C to metal or metal alloy to make (Nb) x Ti 1-x The amount of C is from 1 wt% to 100 wt% of the final product.

8. The method of claim 1 or 2, wherein the metal or metal alloy described in step (Aiv) or (Biii) is below (Nb x Ti 1-x It exists in granular or liquid form at the melting point of C.

9. The method of claim 8, wherein the step of adding the preform to the liquid metal or liquid metal alloy is carried out in the presence of an inert gas or a reduced oxygen partial pressure to avoid oxidation.

10. The method of claim 8, wherein the liquid metal or metal alloy permeates into the voids.

11. The method of claim 1 or 2, wherein the preform is heated to a temperature below the (Nb) x Ti 1-x The step of determining the melting point temperature of C is carried out in the presence of an inert gas or a reduced oxygen partial pressure to prevent oxidation.

12. The method of claim 1 or 2, further comprising curing the metal or metal alloy and (Nb) by cooling the mixture. x Ti 1-x The steps for obtaining the mixture from C.

13. The method of claim 1 or 2, wherein in step (Ai) or (Bi), the (Nb) x Ti 1-x C particles with melting points lower than (Nb) x Ti 1-x A mixture of substances of type C.

14. The method of claim 13, wherein the substance is polyvinyl alcohol.

15. The method of claim 1 or 2, further comprising the steps of adding the master alloy to a liquid metal or metal alloy and dispersing the master alloy in the liquid metal or metal alloy.

16. The method of claim 15, wherein the metal or metal alloy has the same composition as the metal or metal alloy of claim 1 or 2, and has the same or different component concentrations.

Citation Information

Patent Citations

  • Method of producing squeeze castings

    GB1417261A

  • Solid-solution carbide / carbonitride powder and method for preparing thereof

    KR1020100107478A

  • High hardness magnesium alloy composite material

    US20090317622A1

  • Sintered steel alloy

    US4180401A

  • Method of producing metal nanocomposite powder reinforced with carbon nanotubes and the power prepared thereby

    US7217311B2